ISLAMIC RELIGIOUS EDUCATION IN RESPONDING TO THE TRANSFORMATION OF ADOLESCENT RELIGIOSITY IN THE DIGITAL ERA - Fitri Nur Hidayat; Lucky Damara Yusuf (Penelitian dan Pengembangan Ilmu, 2025)
This research abstract analyzes the role of Islamic Religious Education in responding to the transformation of religiousness among adolescents in the digital age through a case study at SMAN 1 Bondowoso. The objectives of this study are to (1) identify the forms of transformation in adolescent religiosity, (2) analyze the role of Islamic religious education teachers in responding to these changes, and (3) reveal the challenges and opportunities in fostering contextual, moderate religiosity rooted in Islamic values. The research used a qualitative method with a case study approach, involving twelve informants from Islamic Religious Education teachers, deputy principals, and students. The results showed that adolescent religiosity underwent a transformation through changes in religious authority sources and more fluctuating worship practices. Islamic Religious Education teachers played an important role in facilitating critical reflection and mediating between normative Islamic teachings and digital reality. This study is expected to contribute to the development of Islamic Religious Education learning strategies that are relevant to the digital development of adolescents.